EFEKTIFITAS PELATIHAN PEMBELAJARAN KIMIA BERBASIS LIFE SKILL DAN CHEMOENTREPRENEURSHIP (CEP) BAGI GURU SMA NEGERI KOTA SEMARANG - Sumarti, Sri Susilogati (Universitas Negeri Semarang, 2012)
This research aim to (1) describe the training model of chemical learning design based on life skill and CEP; (2) know the effectiveness of training model of chemistry learning design based on life skill and CEP. This research use Research and Development (R&D) approach with stages of (1) conduct a preliminary study; (2) design a training model; (3) model validation; (4) testing the model; and (5) describing the final model. Subject of this research were high school chemistry teacher as many as 30 peoples used as a test model of training. Measurement of effectiveness include the variables; (1) ability of the participants in designing learning before and after training; (2) ability to apply chemical learning based on life skill and CEP for trained teachers; (3) participantsâ responses to the implementation of training and skills of trainers. Effectiveness criteria determined by constructing a scale of effectiveness based on the average results of measurements of variables. Data collection techniques using surveys, interviews, and documentation. Instruments used were in the form of questionnaires, observation sheets, interview guidelines, and the researcherâs own instrument. The results can be concluded that the training model of chemical learning design based on life skill and CEP effective to improve the quality of teachers in implementing the chemical learning. Recommended for training providers team that the training model of chemical learning design based on life skill and CEP to be developed within a wider scale.